2020
DOI: 10.1111/ijcp.13735
|View full text |Cite
|
Sign up to set email alerts
|

Nation‐wide analysis of the impact of Covid‐19 pandemic on daily urology practice in Turkey

Abstract: Objective To present a nation‐wide analysis of the workload of urology departments in Turkey week‐by‐week during Covid‐19 pandemic. Methodology The centers participating in the study were divided into three groups as tertiary referral centers, state hospitals and private practice hospitals. The number of outpatients, inpatients, daily interventions and urological surgeries were recorded prospectively between 9‐March‐2020 and 31‐May‐2020. All these variables were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Since the beginning of the pandemic, there has been a remarkable reduction of up to 50% in uro-oncological cases in Europe. In a multicenter study conducted in our country during the pandemic period, a decrease of up to 80% in oncology cases was reported compared to the pre-pandemic period, which was parallel to Europe and the World (21). In this study, by the literature, significant decreases were observed in urooncological cases in both secondary and tertiary hospitals compared to the pandemic period.…”
Section: Discussionsupporting
confidence: 49%
“…Since the beginning of the pandemic, there has been a remarkable reduction of up to 50% in uro-oncological cases in Europe. In a multicenter study conducted in our country during the pandemic period, a decrease of up to 80% in oncology cases was reported compared to the pre-pandemic period, which was parallel to Europe and the World (21). In this study, by the literature, significant decreases were observed in urooncological cases in both secondary and tertiary hospitals compared to the pandemic period.…”
Section: Discussionsupporting
confidence: 49%
“…Elective cases which might require ICU admission were postponed and >55% were operated only if high risk such as obstructing stones and oncology cases (Figure 1). Similarly, in a study by Bozkurt et al, 12 COVID-19 pandemic significantly changed urological practice in Turkey hospitals as priority was given to emergency cases and surgeries which if deferred the course of the disease would affect patient's life. The results of a study recruiting eight academic urological departments in Paris were congruent with our findings where there was a decrease in urological procedures by an overall of 55% in the first year of COVID-19 {oncology surgeries (31%), emergency surgery (44%), reconstructive surgery (85%) and andrology surgery (81%)}.…”
Section: Discussionmentioning
confidence: 98%
“…The workload of hospitals has increased considerably, and governments and hospital systems have taken many healthcare measures to adapt to this load. Many hospitals had to turn to quarantine to serve only COVID-19 patients [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most surgical subspecialties canceled elective surgeries and served only emergency and non-deferrable oncologic surgeries. Social distancing became mandatory in the clinics, and the number of appointments was limited for urgent cases [ 1 ]. In some centers, clinics were prioritized, and non-urgent patients were consulted over Telemedia and postponed for at least six months.…”
Section: Introductionmentioning
confidence: 99%